Desirable banking competition and stability - Benchimol, Jonathan; Bozou, Caroline (Journal of Financial Stability, 2024)
Every financial crisis raises questions about how the banking market structure affects the real economy. Although low bank concentration may reduce markups and foster riskier behavior, concentrated banking systems appear more resilient to financial shocks. We use a nonlinear dynamic stochastic general equilibrium model with financial frictions to compare the transmissions of shocks under different competition and concentration configurations. The results reveal that oligopolistic competition amplifies the effects of the shocks relative to monopolistic competition. The transmission mechanism works through the markups, which are amplified when banking concentration is increased. The desirable banking market structure is determined according to financial stability and social welfare objectives. Moreover, we find that depending on policymakers’ preferences, a banking concentration of five to eight banks balances social welfare and bank stability objectives in the United States.